Service Excellent Pada Usaha yang Berkelanjutan - Agam, Handi; Nirwana, Puspa; Wulan, Saptarining (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2110, 2026)
ABSTRACT Service excellence supports sustainable business by enhancing customer experience, satisfaction, trust, loyalty, and retention while integrating digitalization, innovation, strategic alliances, and sustainability practices to create long-term economic, social, and environmental value. This study aims to analyze the development of the literature on service excellence and its contribution to sustainable businesses, while identifying research gaps and future research directions. The study employs a Systematic Literature Review (SLR) approach. Relevant literature was obtained from various academic databases and analyzed using descriptive analysis and thematic synthesis. The findings indicate that service excellence is associated with customer experience, customer satisfaction, trust, customer loyalty, and customer retention, which can subsequently contribute to business performance and sustainability. The findings also indicate that these relationships can be strengthened through digitalization, innovation, strategic alliances, and sustainability practices. This review highlights the need to expand the concept of service excellence beyond a customer satisfaction-oriented perspective toward long-term value creation that integrates economic, social, and environmental dimensions of business sustainability. Keywords: service excellence, service quality, customer experience, customer loyalty, business sustainability